(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The objectives of this research to determine the effect of transparency on service quality in Department of One Stop Integrated Investment Service and Manpower of Barru Regency. This study conducted quantitative with the survey type, the amount of sample was 58 respondents from the populations with random sampling (simple random sampling). Techniques of Data collection used observation and questionnaire with Likert scale, which has been tested one by one and met the requirements of validity and reliability. Techniques of Data analysis used descriptive statistics and simple linear regression. The results of this study indicated that the effect of transparency on service quality in Department of One Stop Integrated Investment Service and Manpower of Barru Regency has a positive and significant effect.